Aggression is a dominant behavior among adolescents in Al-Sadr city, Baghdad-Iraq - Hassan, Tuka Younis; Ali, Basma M.; Raheem, Ammar Q.; Al-Diwan, Jawad K. (Journal of the Faculty of Medicine Baghdad, 2020)
Background: Aggression is any behavior intending to harm another living being that desires to avoid such harm. Aggression is considered as a public health problem worldwide. Exposure to violence is a determinant of aggression. Al-Sadr city, which is an overcrowded residential area in Baghdad, was exposed to violence through wars, civil war, and widespread inter-personal violence). This situation was an impetus to study aggression in this city. Objectives: To estimate the prevalence of aggression among secondary school students in Al-Sadr city, Baghdad. Methodology: A cross-sectional study was carried out in Al-Sadr city in Baghdad. A total of 720 adolescent secondary schools students from both genders were included in the study. They were selected by multistage random sampling. Their age was ranged from 13-21 years. Data was collected from 1st of February 2019 to 30 of April 2019 through a self-reported questionnaire (Aggression-Problem Behavior Frequency Scale). Results: The mean age of participants was 16.2±2.04 years. Of all participants, 84.3% were assessed to be aggressive; including 329 (91.4%) males and 278 (77.2%) females. Males showed significantly higher aggression than females (p=0.001). Absence from school and low academic achievement were dominating among aggressive students (88.2% and 86.9%, respectively). Non-physical Aggression was the most common type of aggression (76.4%). Conclusion: A high prevalence of aggression (mainly non-physical) was found, which was significantly associated with gender, being higher among males. Aggression was negatively affecting school achievement.